2019
DOI: 10.3390/ijerph16122098
|View full text |Cite
|
Sign up to set email alerts
|

Supervision for Certification in the Field of Applied Behaviour Analysis: Characteristics and Relationship with Job Satisfaction, Burnout, Work Demands, and Support

Abstract: Background: Supervision of behavior analysts seeking certification and supervision of service delivery are key processes in the provision of quality behaviour analytic services to individuals with developmental disabilities. Our study is the first to examine international supervisory practices within the field of applied behaviour analysis. Method: An online survey was distributed to 92 professionals internationally, assessing supervisory practice, supervisor support, work demands, job satisfaction, and burnou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
(64 reference statements)
2
9
1
1
Order By: Relevance
“…We compared the cost of providing behavior-analytic treatment in-situ versus via telehealth to assess the cost effectiveness of telehealth-based interventions. We calculated the hourly rate of the BCBA ® (Dounavi et al, 2019), the cost of equipment, and the travel costs associated with providing treatment in-situ. The hourly rate was converted from Euros to United States dollars (€1.00 = $1.27 as of January 18 th , 2021) and multiplied by the total number of treatment hours provided.…”
Section: Cost Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…We compared the cost of providing behavior-analytic treatment in-situ versus via telehealth to assess the cost effectiveness of telehealth-based interventions. We calculated the hourly rate of the BCBA ® (Dounavi et al, 2019), the cost of equipment, and the travel costs associated with providing treatment in-situ. The hourly rate was converted from Euros to United States dollars (€1.00 = $1.27 as of January 18 th , 2021) and multiplied by the total number of treatment hours provided.…”
Section: Cost Analysismentioning
confidence: 99%
“…The cost of one set of headphones and one camera totaled $115.87 (€95.58) with an additional $27.28 (€22.50) for postage (tracked and signed for), making the total cost for purchasing and sending the equipment $143.15 (€118.08). The average hourly rate for a behavior analyst in Europe is between €0-75 (Dounavi et al, 2019;$0-91.69) and due to the limited amount of BCBA ® s available in some European countries, families and specialist schools and clinics who can afford it often pay for the travel of a BCBA ® . Travel expenses have been incorporated into Figure 4.…”
Section: Cost Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Plantiveau et al also reported some conditions that tended to meliorate burnout and job dissatisfaction, including support at work from supervisors and peers, opportunities for professional development, and high-quality supervision. Dounavi et al (2019) extended this research to a sample of 92 international behavior analysts. They reported that across the three dimensions of burnout, emotional exhaustion, depersonalization, and personal accomplishment, 37%, 37%, and 27%, respectively, experienced burnout.…”
Section: Burnout In Behavior Analysismentioning
confidence: 99%